Evaluation of barley genotypes for the content of β-glucans in grain and other valuable features in Eastern Siberia - V. I. Polonskiy; N. A. Surin; S. A. Gerasimov; A. G. Lipshin; A. V. Sumina; S A. Zute (Труды по прикладной ботанике, генетике и селекции)
Background. The aim of the research was to identify barley germplasm accessions with the minimum and maximum content of β-glucans in their grain in combinations with other improved useful traits.Material and methods. The material for analysis were 18 hulled and 8 naked barley accessions of various ecogeographic origin from the collection of the N.I. Vavilov All Russian Institute of Plant Genetic Resources (VIR), which were grown under the conditions of Eastern Siberia in 2016–2018.Results. Hulled accessions yielded grains with β-glucan content from 3.18 to 4.51%; naked ones, from 3.18 to 5.21%. According to the minimum value of the studied qualitative trait (3.18–3.43%), cultivars of Siberian breeding were identified: ‘Mayak’ (k-29622, Krasnoyarsk Territory) and ‘Tarsky 3’ (k-30719, Omsk Province), plus cv. ‘AC Albright’ (k-30599, Canada); according to the maximum value (5.06–5.21%), the naked accessions Nudum 155 (k-13328, Ukraine) and ‘Nudum 95’ (k-31125, Chelyabinsk Province). The highest protein content in grain (16.63–18.36%) was found in the accessions Nudum 155, Nudum 7566 (k-29453, Kyrgyzstan) and ‘Nudum 95’. The accessions Nudum 155 and ‘Nudum 95’ were characterized by combined high contents of β-glucans and protein in their grain. Early maturity and increased productivity were shown by the cultivars ‘Tarsky 3’, ‘Kolchan’ (k-31039, Altai Territory), ‘Zolotnik’ (k-30845, Altai Territory), ‘Abalak’ (Krasnoyarsk Territory, Tyumen Province), and ‘AC Albright’ (Canada). A significant positive relationship was found between the content of β-glucans and the weight of 1000 grains in both forms of barley.Conclusion. According to β-glucan content combined with other valuable characteristics in grain, the accessions ‘Mayak’, ‘Tarsky 3’ and ‘AC Albright’ are of interest for the improvement of fodder cultivars, while ‘Nudum 95’ and Nudum 155 are promising for breeding for food.